Locke and the education of the adolescent - Francisco T. Baciero Ruiz (FahrenHouse, 2008)
John Locke has been considered one of the leading figures in the His- tory of Philosophy, specially for his two famous treatises An Essay concerning Human understanding and Two Treatises on Government. None the less his work in Pedagogy, Some thougths concerning Education, is no less important, and provides the leading strings of that what ought to be the education of the gentleman, whose unavoidable foundation must be a solid education in virtue grounded in the moral principles of Christianity. Key words: Locke, Moral education, Spanish authors of the XVIth century.